Ekfraza jako bohater parodii (o kilku wierszach Olgerda Dziechciarza) - Grodecka, Aneta (Wydawnictwo Naukowe UAM, 2009)
The appearance of the parody of poetic ekphrasis is an important argument in disputes concerning its status. The author considers Olgerd Dziechciarz's collection of poems Galeria "Humbug" [The "Humbug" Gallery] as a missing link of reconstruction of the genre, referring to her own studies conducted as a post-graduate work Wiersze o obrazach. Studium z dziejów ekfrazy [Poems on pictures. A study in the history of ekphrasis] (in preparation). In the course of the analysis the author referred to paintings (H. Bosch, P. Cezanne, Michelangelo), other poetic commentaries of C. Miłosz, A. Stern as well as studies on art (among others D. Freedberg, F. Arnau), considering mainly the problems connected with the reception of pictures.
Ekphrasis as a potagonist of parody - on some poems of Olgerd Dziechciarz